RADH-A Reversible and Authenticable Data Hiding Scheme in Encrypted Domain Based on Image Interpolation and Substitution - Chia-Chen Lin; Rong-Ze Chen; Wei-Liang Tai; Chun-Jung Lin (Applied Sciences, 2024)
The rise of the Internet has transformed communication and information access, but it also raises serious privacy concerns, especially regarding personal image sharing. This paper presents a novel reversible and authenticable data-hiding scheme for encrypted images that utilizes interpolation techniques and substitution methods. Our encryption system achieves a lower correlation among neighboring pixels, ensuring a more uniform distribution in the encrypted image. The stego images do not reveal any information about the original cover image or secret data. The embedded authentication data provides the ability to verify the authenticity of the image and localize the tampering. Experimental results show that our scheme can securely protect an image from unauthorized access and verify its authenticity.